2008
DOI: 10.1002/pits.20337
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' collaboration in the classroom: Do peer relationships or gender matter?

Abstract: Peer collaboration can be a useful tool in a school classroom to help students perform at their best. With whom should students be paired, though? Previous research yields inconsistent findings regarding whether the benefits of peer collaboration depend on the gender or friendship of collaborators. We paired students with a same-gender friend or a nonfriend in their classroom to examine whether friendship and specific dimensions of relationship quality were important for understanding adolescent (N = 132 high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…A review of literature shows mixed findings with regard to the question of whether groups of friends perform better or worse than groups of acquaintances. Whereas some studies have documented a positive effect of friendship on group performance (e.g., Harrison, Mohammed, McGrath, Florey, & Vanderstoep, 2003; Jehn & Shah, 1997; Shah & Jehn, 1993), other studies have not documented performance benefits of friendship groups (e.g., Andersson & Rönnberg, 1996; Nibler & Harris, 2003; Peker & Tekcan, 2009; Swenson & Strough, 2008).…”
mentioning
confidence: 98%
“…A review of literature shows mixed findings with regard to the question of whether groups of friends perform better or worse than groups of acquaintances. Whereas some studies have documented a positive effect of friendship on group performance (e.g., Harrison, Mohammed, McGrath, Florey, & Vanderstoep, 2003; Jehn & Shah, 1997; Shah & Jehn, 1993), other studies have not documented performance benefits of friendship groups (e.g., Andersson & Rönnberg, 1996; Nibler & Harris, 2003; Peker & Tekcan, 2009; Swenson & Strough, 2008).…”
mentioning
confidence: 98%
“…In other studies of Cornish, (2009), Gnadinger, (2008), revealed that in modern era multigrade classrooms, the basic philosophy of classroom organization. In research studies of Many and Henderson, Swenson and Strough, (2008), the finding in the theoretical basis that student learn best through differential instruction and social interaction and peer collaboration. In another research study of Cheadle, (2008), the socioeconomic status factor has long had an influence on student achievement.…”
Section: Discussion:-mentioning
confidence: 99%
“…On the one hand, cognitive tasks may heighten the positive effect of friends on group performance because friends should feel more comfortable engaging in cognitive activities such as problem solving (e.g., Azmita & Montgomery, 1993) or memory retrieval tasks (e.g., Andersson, 2001) as compared to non-friends. On the other hand, cognitive tasks may attenuate the positive effect of friends on group performance because friends tend to be less comfortable engaging in effective reasoning techniques when completing problem solving tasks (e.g., Swenson & Strough, 2008).…”
Section: Figure 2 Summary Of Hypotheses and Conceptual Framework Expmentioning
confidence: 99%
“…However, current research lacks consensus regarding the positive or negative effect of friendship on group performance. While some research has suggested a positive effect of friendship on group performance (e.g., Jehn & Shah, 1997;Shah & Jehn, 1993;Harrison, Mohammed, McGrath, Florey, & Vanderstoep, 2003), other research has documented that friendship negatively impacts performance (e.g., Andersson & Ronnberg, 1995;Swenson & Strough, 2008). In light of these mixed findings, the overall effect of friendship on group performance remains unclear.…”
Section: Introductionmentioning
confidence: 99%